IMPACT OF ANTIMICROBIAL STEWARDSHIP PROGRAM ON THE USE OF ANTIBIOTICS IN PNEUMONIA PATIENTS AT TEACHING HOSPITAL IN SURAKARTA INDONESIA - KARUNIAWATI, HIDAYAH; YULIANTI, TRI; AINI, DEWI KUROTA; NURWIENDA, FINISHIA ISNA (International Journal of Applied Pharmaceutics, 2021)
Objective: Antibiotic resistance is a serious problem worldwide. One cause of antibacterial resistance is the inappropriate use of antibiotics. The study of antibiotic use in hospitals found that 30–80% were not based on indications. Antimicrobial Stewardship Programs (ASP) was developed to control antimicrobial resistance. This study aims to evaluate the impact of ASP in pneumonia patients qualitatively and quantitatively pre-post ASP applied. Methods: This research is a non-experimental study. Data were taken from the medical records of pneumonia patients and analyzed qualitatively using the Gyssens method and quantitatively using the Defined Daily Dose (DDD) method. Sampling was conducted through purposive sampling and results were described descriptively. Results: During the study period, 96 samples were obtained with 48 data pre-ASP and 48 data post-ASP. The results of the qualitative analysis using the Gyssens method show an increase in the prudent use of antibiotics from 31.25% to 62.5% pre-post ASP, respectively. Quantitative evaluation shows a decrease of antibiotic use pre-post ASP from 90.84 DDD/100 patients-days to 61.42 DDD/100 patients-days. Conclusion: The ASP can improve the quality of antibiotic use in pneumonia patients quantitatively and qualitatively.